Dynamic thermal-hydraulic simulations of the JT-60SA cryogenic system for preparing plasma operation. (April 2019) - Bonne, F.; Hoa, C.; Nicollet, S.; Zani, L.; Vallet, J-C; Di Pietro, E.; Wanner, M.
Abstract: Recent measurements on the JT-60SA toroidal field coils showed a slightly higher pressure drop than expected, resulting in a lower supercritical helium mass flow rate during normal plasma operation. This paper presents some simulations of the cooling loop considering these updated thermal-hydraulic parameters and the expected pulsed heat loads. The model includes a cold circulator, heat exchangers, helium thermal buffer, the distribution system and the superconducting coils. The article presents the differences between the initial scenario which was validated during commissioning of the cryogenic system and the updated scenario to prepare plasma operation with the cryo-magnetic system. The simulation also provides the transient heat load profiles of the cooling loop, highlighting a first smoothing of the thermal loads at the interface with the cryogenic system. The Simcryogenics code, developed at CEA Grenoble, is used to simulate the dynamic loads.